Specificities of the impact of a crisis situation on the development of self-esteem in adolescence - Fomicheva D. D. (Sormovo Readings- 2025: scientific and educational space, realities and prospects for improving the quality of education, 2025)
In the article, the author provides a brief analysis of theoretical provisions on the types of crisis situations and the specificities of the development of self-esteem in adolescence. The purpose of the article is to reveal the theoretical aspects of the concepts of "crisis situation" and "self-esteem", to identify the factors influencing the crisis situation on the self-esteem of a teenager.
Keywords: самооценка; личность; подросток; самопознание; personality; подростковый возраст; индивид; individual; кризис; crisis; self-esteem; самовосприятие; teenager; self-knowledge; adolescence; кризисная ситуация; crisis situation; self-perception; personality crisis; личностный кризис